A wide-band high-Q dispersive delay line for square-wave signals - Pookaiyaudom, S.; Kuhanont, T. (My University, 1978)
A long delay line, having controllable dispersive characteristics, suitable for delaying wide–band square–wave signals using only a single adaptive delay element, is proposed and experimentally demonstrated. © 1978 Taylor and Francis Group, LLC.